Determinants of Low Birth Weight (LBW) in Majene Regency - Aryanti, Novi; Annisa, Nurul; Zakiah, Nur; Supyati, Supyati (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Low birth weight (LBW) is an important health problem, particularly in developing countries with low socioeconomic conditions. This study aimed to analyze maternal factors associated with the incidence of LBW in Majene Regency in 2023. The study involved 90 subjects selected through total sampling, using a case–control design and chi-square analysis. The results showed that maternal anemia was significantly associated with LBW (p-value<0,05), whereas maternal age, height, MUAC, exposure to cigarette smoke, and education were not associated (p-value>0,05). These findings emphasize the importance of educating pregnant women to regularly consume iron (Fe) tablets correctly, such as taking them before bedtime and avoiding consumption together with tea or coffee.